Literature Review of ISO 26000 Corporate Social Responsibility (CSR) and Implementation Recommendations to the Defense Industries - Sugianto, Sugianto; Soediantono, Dwi (Journal of Industrial Engineering & Management Research, 2022)
The purpose of this article is to explore the benefits of implementing and benefitting ISO 26000 Corporate Social Responsibility (CSR) in various industries and provide suggestions to be applied to the defense industry. The method of writing this article is a literature review, which is a review by collecting, understanding, analyzing and then concluding as many as 30 international journal articles on Corporate Social Responsibility (CSR) published from 2015 to 2021 regarding the application of the Corporate Social Responsibility (CSR) method in various industrial sectors and the defense industry. . The analysis used used 25 content analysis of journal articles. The results of the literature review analysis state that the implementation of ISO 26000 Corporate Social Responsibility (CSR) can have benefits for companies, society and the government, namely maintaining and boosting the company's reputation and brand image, obtaining a license to operate socially, reducing the company's business risks, expanding access to resources. for social operations, opening up wider market opportunities, reducing costs, for example costs associated with the impact of waste disposal, improving relations with stakeholders, improving relations with regulators, increasing employee morale and productivity, increasing opportunities for awards. ISO 26000 Corporate Social Responsibility (CSR) is recommended to be applied in the defense industry